Pengaruh Aktivitas, Struktur Modal, Likuiditas Dan Ukuran Perusahaan Terhadap Pertumbuhan Perusahaan Pada Emiten Sektor Transportasi Dan Logistik Tahun 2017-2021 - Tesya Faradilla; Irham Lihan; Ahmad Faisol (CV. Multi Kreasi Media, 2023)
This study will look at the effects of activity, capital structure, liquidity, and firm size on company growth in the transportation and logistics sector for the period from 2017 to 2021. In this analysis, the population corresponds to the sector issuers for logistics and transportation from 2017 to 2021. The purposive selection method was used to choose the research sample, which consisted of 12 firms that would be the focus of the investigation. The Indonesian Stock Exchange provided the secondary data for the research. In this study, the analytic method included the use of descriptive statistics, classical assumption testing, panel data regression analysis testing, model testing and hypothesis testing. The dependent variable being assessed is sales growth, while the independent variables are working capital turnover, long term debt to equity ratio, the current ratio, and the logarithm of total assets. This study's conclusion is that, at a level of significance of 5%, activity, capital structure, and firm size all positively affect company growth. While the company growth is unaffected by liquidity.